2014
DOI: 10.1289/isee.2014.o-280
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Neighborhood Green Space and Mental Health: Evidence from the Survey of the Health of Wisconsin

Abstract: Green space is now widely viewed as a health-promoting characteristic of residential environments, and has been linked to mental health benefits such as recovery from mental fatigue and reduced stress, particularly through experimental work in environmental psychology. Few population level studies have examined the relationships between green space and mental health. Further, few studies have considered the role of green space in non-urban settings. This study contributes a population-level perspective from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 35 publications
2
100
0
5
Order By: Relevance
“…Previous research has established a substantial link between exposure to nature (e.g., trees, shrubbery, grass, parks) and better physical and mental health, including improved cognitive and behavioral functioning (e.g., Kelz, Evans, & Röderer, ; Mårtensson et al., ; Roe & Aspinall, ). The advantages of nature exposure for adults’ physical and mental health have been well documented (e.g., Beyer et al., ; Ward Thompson et al., ), and some work has even found that residents in neighborhoods with more natural elements report greater social capital (i.e., neighborhood‐level connections and association; Holtan, Dieterlen, & Sullivan, ). Although some evidence suggests that nature exposure may support healthy child development as well (e.g., Gill, ), this research base is less developed, and very few studies examine the relationship between nature near or surrounding schools and early childhood development.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has established a substantial link between exposure to nature (e.g., trees, shrubbery, grass, parks) and better physical and mental health, including improved cognitive and behavioral functioning (e.g., Kelz, Evans, & Röderer, ; Mårtensson et al., ; Roe & Aspinall, ). The advantages of nature exposure for adults’ physical and mental health have been well documented (e.g., Beyer et al., ; Ward Thompson et al., ), and some work has even found that residents in neighborhoods with more natural elements report greater social capital (i.e., neighborhood‐level connections and association; Holtan, Dieterlen, & Sullivan, ). Although some evidence suggests that nature exposure may support healthy child development as well (e.g., Gill, ), this research base is less developed, and very few studies examine the relationship between nature near or surrounding schools and early childhood development.…”
Section: Introductionmentioning
confidence: 99%
“…Summary of the results regarding associations between living environment/neighbourhood and depressive mood in the 57 studies included in the systematic review. Higher level and speed of urbanization was related to depressive symptoms, even when individual characteristics were considered(Chen et al, 2014) • • Residents of metropolitan areas had increased risk of a major depressive episode compared to those residing in the countryside or in county towns, Residents of micropolitan and rural areas had depressive symptoms more often than residents of metropolitan areas, even after adjustments for individual and neighbourhood characteristics(Beyer et al, 2014) Individuals with deck access (vs other types), living in properties built in 1970 or later (vs pre-1940) had higher risk of depression after adjustments for socioeconomic status, floor of residence and structural housing problems(Weich et al, 2002) • • Objective neighbourhood deterioration was associated with significantly lower depressive symptoms, whereas perceived neighbourhood deterioration was associated with significantly higher depressive symptoms, after adjustments for Having structural problems in relation to housing conditions, lacking separate kitchen and proper toilet and bathroom facilities were associated with high levels of depression, after adjustments for age, gender, marital status, employment and migratory status(Firdaus & Ahmad, 2014) • • Percentage of housing units with some non-functioning kitchen facilities, heat breakdowns and requiring additional heat in winter, large areas of peeling plaster or paint, buildings in an observed deteriorating condition and number of structural fires were related to current and lifetime depression after…”
mentioning
confidence: 99%
“…The existence of greenspace in neighborhood environment, such as tree canopy, parks and forests, has found to be associated with better physical health, reduction in morbidity in some disease categories, lower level of depression, lower level of stress, and so on (e.g., [4]; [70]. In fact, the roles of greenspace have found to be especially significant in protecting building occupants from health hazards related to air pollution and extreme temperature (e.g.…”
Section: Neighborhood Environment and Building Occupantsmentioning
confidence: 99%